2013
DOI: 10.2355/isijinternational.53.603
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model for the Reduction Stage of the AOD Process. Part I: Derivation of the Model

Abstract: A process model was proposed by Järvinen and co-authors for modelling the side-blowing decarburisation stage of the Argon-Oxygen Decarburisation (AOD) process. Here, a new model for the reduction stage has been derived and coupled with the earlier-developed model. The model considers mass-transfer controlled reversible reactions between the steel bath and the top slag. The effect of emulsification phenomena on the total reaction area and on the mass and heat transfer characteristics have been taken into accoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Chromium recovery is possible inside AOD converter during reduction stage when only inert gas is purged. Visuri et al have modeled mathematically for the reduction stage of the AOD process, according to them the reduction rate of chromium oxides is controlled initially by mass transfer of silicon onto the reaction surface and later by the diffusive mass transfer of chromium oxides in the slag droplets …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromium recovery is possible inside AOD converter during reduction stage when only inert gas is purged. Visuri et al have modeled mathematically for the reduction stage of the AOD process, according to them the reduction rate of chromium oxides is controlled initially by mass transfer of silicon onto the reaction surface and later by the diffusive mass transfer of chromium oxides in the slag droplets …”
Section: Introductionmentioning
confidence: 99%
“…Visuri et al have modeled mathematically for the reduction stage of the AOD process, according to them the reduction rate of chromium oxides is controlled initially by mass transfer of silicon onto the reaction surface and later by the diffusive mass transfer of chromium oxides in the slag droplets. [4,5] Nitrogen in steel melt is increased to the range of 1000-1500 ppm during nitrogen injection period as stainless steel has high equilibrium nitrogen concentration. Nitrogen can be used as substitute to nickel as nickel is costlier than nitrogen so using nitrogen reduces the production cost and sometime enhances toughness.…”
Section: Introductionmentioning
confidence: 99%
“…22,23) The method has also been applied for mathematical modelling of chemical heating in the CAS-OB process. 24) The traditional equilibrium coefficient method would be to insert these activities as the boundary condition at the reaction surface and then solve the non-linear system of equations.…”
Section: Applications and Comparison To Existing Approachesmentioning
confidence: 99%
“…As stated in the derivation of the model, 6) the plume diameter and the interfacial velocity at the steel-slag interface are considered independent from the gas flow rate. Therefore, the gas flow rate has no direct influence on the emulsification phenomena.…”
Section: Validation Datamentioning
confidence: 99%
“…In Part I, 6) it was concluded that although numerous reaction models have been developed for the AOD process, there are only a few models that explicitly cover the emulsification of slag and rate phenomena during the reduction stage. Then, using an approach based on the modified law of mass action, a new mathematical model for the reduction stage was proposed and coupled with the mathematical model for side-blowing decarburisation developed by Järvinen et al 7,8) This paper, Part II, focuses on the validation of the model with full-scale production data from a 150 t AOD converter at Outokumpu Stainless Oy, Tornio Works, Finland.…”
Section: Introductionmentioning
confidence: 99%